El Romancero aux étoiles de Jacques Stephen Alexis como sutura de una nación escindida - Viterbo, Florencia Romina (2020)
En 1960, Jacques Stephen Alexis, como continuador del indigenismo haitiano cuya piedra angular es el Ainsi parla l'oncle de Jean Price Mars, publica Romancero aux étoiles, un libro de relatos en donde invita a un lectorado culto a defender las raíces de lo popular haitiano, para suturar una nación escindida en una acomodada elite urbana y una masa analfabeta de campesinos. Entrelazando una oralidad de rasgos populares con una escritura neobarroca, esta publicación implica un gesto político nacionalista: en el contexto de la sangrienta dictadura de François Duvalier, Alexis exalta el ámbito rural y lo considera un arma poderosa para defender la identidad nacional frente a la cultura imperialista extranjera, que avanza auspiciada por el régimen duvalierista.
In 1960, Jacques Stephen Alexis, as a continuator of Haitian indigenism whose cornerstone is Ainsi parla l'oncle of Jean Price Mars, publishes Romancero aux étoiles, a book of stories where he invites a culted scholar to defend the roots of the popular Haitian, to suture a nation split into a wealthy urban elite and an illiterate mass of peasants. Intertwining an orality of popular features with a neo-baroque writing, this publication implies a nationalist political gesture: in the context of the bloody dictatorship of François Duvalier, Alexis exalts the rural realm and considers it a powerful weapon to defend national identity against culture foreign imperialist, which advances under the auspices of the Duvalier regime.
Keywords: Literatura haitiana; Jacques stephen alexis; Cultura popular; Regimen duvalierista; Identidad haitiana; Haitian literature; Jacques Stephen Alexis; Popular culture; Haitian identity; Duvalier Regime